Experimental investigation of gas lift technique in viscous fluids - Ibrahim, Abubakr (2017)
Oil and gas often naturally flow to the surface driven by the high pressure of the reservoir. Over the time oil fields suffer a decline in production primarily caused by the decrease in the reservoir pressure coupled with the fact that fluids become thicker and more viscous. In addition, there are huge reserves of oil that have not been exploited because of the high drilling and pumping costs owing to the high viscosity and density of the oils within. The feasibility of drilling new wells or continuing production from ’dead’ reservoirs depends to a great extent on the pumping cost. Pumping is achieved via several methods including gas-lift. It is applied by injecting gas to the base of the oil well which in turn reduces the weight of the oil column in the well riser. The decrease in pressure head results in an increased liquid flow.